Effects of vertical and horizontal strength exercises on sprint performance and sprint mechanical outputs in amateur soccer players - Marcin Krawczyk; Mariusz Pociecha; Jamie Tallent; Uzo Dimma Ehiogu (Journal of Kinesiology and Exercise Sciences)
Background: The aim of this study was to investigate the effects of combined vertical and horizontal strength exercises on sprint mechanical parameters and sprint performance among amateur soccer players. Methods: The study followed a controlled experimental design. Twenty amateur soccer players were assigned to either an experimental group (EG, n = 11) or a control group (CG, n =9). In addition to the soccer training, the EG group conducted a sixweek training program involving combined horizontal and vertical strength exercises. Sprint performance and sprint mechanical parameters were computed using a field method based on velocity-time data pre- and post-intervention. The repeated measures ANOVA test was used for between-group comparisons. Results: The results suggest a significant (p < 0.05) improvement in sprint performance at 0-10 meter distance (p = 0.02), 0-15 meter distance (p = 0.01), 0-20 meter distance (p = 0.03), and the maximal value for the ratio of force - RFmax (p = 0.03) in EG compared to CG. Conclusions: The horizontal and vertical strength exercises can improve sprinting performance at distances longer than 5 m but do not improve the most of examined mechanical sprinting parameters in amateur soccer players.